4CPS-343 Pregabalin and gabapentin drug utilisation review. (14th March 2021) - Murphy, D; Kieran, M; Brown, J
Abstract : Background and importance: The Health Service Executive Medicines Management Programme has highlighted the need for vigilance when prescribing and dispensing pregabalin or gabapentin as both drugs have a risk of addiction and a potential for misuse/abuse. A recent systematic review found that reports of pregabalin and gabapentin abuse are increasingly being documented worldwide. 1 Aim and objectives: To examine the pharmacy supply of pregabalin/gabapentin over the past 4 years to determine if usage has increased; and to assess if pregabalin/gabapentin is being initiated for patients inhouse, what doses are being used and if prescribed for epilepsy. Material and methods: Reports on pregabalin/gabapentin use in the previous 4 years were generated from the pharmacy information system. A 1 day hospital-wide review of pregabalin/gabapentin prescribing was conducted in August 2018. A data collection form was designed to collect information on the number of patients prescribed pregabalin or gabapentin, the dose prescribed, if treatment was started prior to hospital admission and if the patient had a history of epilepsy. Clinical pharmacists completed the data collection by examining the drug chart and the medical notes. Results: Hospital usage of pregabalin and gabapentin increased by 7% and 16%, respectively, from 2015 to 2018. 588 inpatient drug charts were included. 53 patients were prescribed pregabalin, 1 of whom had a history of epilepsy. 83% of pregabalin prescriptions were initiated before hospital admission. 45 patients were prescribed gabapentin. Five patients had a history of epilepsy. 47% of gabapentin prescriptions were initiated before hospital admission. Conclusion and relevance: Hospital prescribing of pregabalin and gabapentin has increased since 2015. The high rate of gabapentin initiation reflects the hospital postoperative pain guidelines. In contrast, most patients were commenced on pregabalin prior to hospital admission. The results suggest that pregabalin and gabapentin are rarely prescribed for epilepsy. These results were disseminated to the Drug and Therapeutics Committee. Interventions for appropriate use will be explored. This review will provide baseline data for which future reviews can be compared against. References and/or acknowledgements: Evoy K, Morrison M, Saklad S. Abuse and misuse of pregabalin and gabapentin. Drugs 2017; 77 : 403–26 Conflict of interest: No conflict of interest